SISTEM KEWARISAN HAZAIRIN DAN TOHA YAHYA OMAR SERTA KONTRIBUSINYA DALAM PEMBENTUKAN UNDANG-UNDANG KEWARISAN DI INDONESIA - Miswanto Miswanto; Fathul Mu’in (Nizham Jurnal Studi Keislaman, 2021)
Until now, Indonesia has adhered to three types of inheritance law, namely Civil Law Inheritance (BW), Islamic Inheritance Law and Customary Inheritance Law. In Islamic inheritance law, it is known that there are two major ideas that are mutually different, namely the thoughts of Hazairin and Toha Yahya Omar. This begins with the use of different methods of interpretation between the two resulting in different legal products. This type of research is library research, descriptive analytic and comparative. As for getting the required data, it is done by searching books or scientific works related to the topic of discussion. After the data was collected, a qualitative analysis was carried out. And finally to draw conclusions, deductive-inductive methods are used. The research results show that Hazairin with his new ijtihad pattern has been able to provide an alternative understanding that is more systematic, coherent and comprehensive with the aim of creating a more universal system without the slightest bit of discrimination in it, namely a bilateral individual inheritance system. Meanwhile, M. Toha Yahya Omar remains consistent with the results of the ijtihad of the Sunni ulama with the Syafii sect, which concludes that the inheritance system which is considered in accordance with the text of the Quran is the Individual Patrilineal inheritance system.